2009
DOI: 10.2298/avb0904413p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on profile of serum proteins in the calf

Abstract: The authors studied the course of serum proteins during the first week and the first month of life in the calf in order to obtain useful information for neonatal care. Eight Limousine calves, four males and four females, clinically healthy, were used. From all animals blood samples were collected from the external jugular vein from the day after the birth every day for one week and every five days for thirty days. Blood samples were taken at the same hour (09:00), and the serum concentrations of albumin, globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…It has been stated in most animal species that the values of serum proteins at birth are low due to the ineffective transfer of immunoglobulins through the placenta and low values of albumin [21,22]. In the present study, no marked differences in the values of total proteins were observed in newborn ruminants and the values were comparable to those detected by Franklin et al [23] and Piccione et al [16] in calves, and by Chen et al [24] and Nagy et al [25] in small ruminants. On the other hand, the values recorded in neonatal piglets were significantly lower and about the half of values measured in newborn ruminants.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It has been stated in most animal species that the values of serum proteins at birth are low due to the ineffective transfer of immunoglobulins through the placenta and low values of albumin [21,22]. In the present study, no marked differences in the values of total proteins were observed in newborn ruminants and the values were comparable to those detected by Franklin et al [23] and Piccione et al [16] in calves, and by Chen et al [24] and Nagy et al [25] in small ruminants. On the other hand, the values recorded in neonatal piglets were significantly lower and about the half of values measured in newborn ruminants.…”
Section: Discussionsupporting
confidence: 85%
“…Most of the studies dealing with the fractionation of serum proteins in neonatal ruminants were oriented to the interpretation of dynamic changes of serum protein fraction in a short period after birth [16,18]. Precolostral serum samples were not standardly collected and possible species-related differences among newborns of farm animals were not yet described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional management before calving is necessary to prepare the cow for subsequent lactation and to prevent metabolic disorders (Cardoso et al 2020). Manipulating the composition of colostrum through dietary intervention and/or mineral supplementation is likely to alter lipid composition (Haug et al 2007) and provide additional immunity to the neonate (Piccione et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing exposure to pathogens, improving immunity, and applying chemotherapeutic agents are focus areas in calf and heifer management (Earley & Fallon, 1999). Calves have little or no immunity at birth, and colostrum is a crucial source of immunoglobulins for initiating innate defence systems (Lawrence & Pierce, 1983;Piccone et al, 2009). However, early establishment of innate immunity in confined dairy calf management systems is often associated with failure of availability of colostrum and a low rate of intestinal absorption of IgG (Godden, 2008;Piccone et al, 2009).…”
Section: Introductionmentioning
confidence: 99%